Alteration of protein homeostasis mediates the interaction of Pseudomonas aeruginosa with Staphylococcus aureus. Issue 3 (8th May 2020) - Yang, Nana; Cao, Qiao; Hu, Shuyang; Xu, Chenchen; Fan, Ke; Chen, Feifei; Yang, Cai‐Guang; Liang, Haihua; Wu, Min; Bae, Taeok; Lan, Lefu
Abstract: Intracellular protein degradation is essential for the survival of all organisms, but its role in interspecies interaction is unknown. Here, we show that the ClpXP protease of Pseudomonas aeruginosa suppresses its antimicrobial activity against Staphylococcus aureus, a common pathogen co‐isolated with P. aeruginosa from polymicrobial human infections. Using proteomic, biochemical, and molecular genetic approaches, we found that this effect is due to the inhibitory effects of ClpXP on the quorum sensing (QS) of P. aeruginosa, mainly by degrading proteins (e.g., PhnA, PhnB, PqsR, and RhlI) which are critical for the production of QS signal molecules PQS and C4‐HSL . We provide evidence that co‐culturing with S. aureus induces a decrease in the activity of ClpXP in P. aeruginosa, an effect which was also achieved by the treatment of P. aeruginosa with N‐acetylglucosamine (GlcNAc), a widespread chemical present on the surface of diverse cell types from bacteria to humans. These findings extend the range of biological events governed by proteolytic machinery to microbial community structure, thus also suggesting that a chemical‐induced alteration of protein homeostasis is a mechanism for interspecies interactions. Abstract : In nature, bacteria often form complex communities where interactions between different species have important roles in shaping the overall behavior of the microbial community. Here, we show that GlcNAc‐induced inhibition of ClpXP causes an activation of the Pqs and Rhl quorum‐sensing systems in Pseudomonas aeruginosa, resulting in an increase in the antimicrobial activity of this important human pathogen. Thus, the chemical‐induced alteration of protein homeostasis may represent a new mechanism for interspecies interactions.